ROLES AND RIGHTS OF WOMEN DURING VEDIC AND POST-VEDIC AGE - Dr. Maitreyee Goswami (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Every individual should have some amount of freedom in the society. Woman constitutes a half of the total population in a society. As such to acertain how cultured and progressive the society is, it is essential to find out as to how is the status of women in that particular society. In this paper an attempt is made to find out the roles and rights that women enjoyed from Vedic to post Vedic period i.e., the status that they enjoyed in different stages especially in Indian context. Here description is given of different women and their happiness-sorrows, pain-pleasure, status-position and different things which they experienced in their daily life.